2020
DOI: 10.4038/seajme.v14i2.243
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Medical Education: Insights and Recommendations

Abstract: Disruptions in medical education are inevitable as healthcare systems across the world are set to be further stretched with the increasing burden of COVID-19 pandemic. Given the risks of nosocomial infection and other unique, similar challenges, there is difficulty in adapting required changes in medical education, particularly for the medical students and training junior doctors. This paper discusses the different elements affecting and the widespread impact of COVID-19 pandemic on medical education. It concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Since the COVID-19 pandemic, disruptions in medical education were unavoidable. Adaptations of the medical education system among health care learners were developed [ 1 ], including long distance or online learning, telemedicine, e-learning [ 2 ], online video lecture [ 3 ], and online synchronous live streaming sessions [ 4 ]. Niriella et al [ 1 ] suggested that a medical education program during the COVID-19 pandemic should be flexible and involve collaboration between learners and facilitators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the COVID-19 pandemic, disruptions in medical education were unavoidable. Adaptations of the medical education system among health care learners were developed [ 1 ], including long distance or online learning, telemedicine, e-learning [ 2 ], online video lecture [ 3 ], and online synchronous live streaming sessions [ 4 ]. Niriella et al [ 1 ] suggested that a medical education program during the COVID-19 pandemic should be flexible and involve collaboration between learners and facilitators.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptations of the medical education system among health care learners were developed [ 1 ], including long distance or online learning, telemedicine, e-learning [ 2 ], online video lecture [ 3 ], and online synchronous live streaming sessions [ 4 ]. Niriella et al [ 1 ] suggested that a medical education program during the COVID-19 pandemic should be flexible and involve collaboration between learners and facilitators. Due to the COVID-19 pandemic face-to-face lectures in 2020 were forcibly changed to online lectures via Zoom the following year.…”
Section: Introductionmentioning
confidence: 99%